The Quality Control At Keripik Tempe Abadi Malang - Muhammad Ramadhany; Aniek Rumijati; Triningsih Sri Supriyati (Universitas Muhammadiyah Malang, 2021)
Changes in the industrial world such as the emergence of the Coronavirus have had a huge impact on companies because consumers are more selective in choosing good quality products for consumption. Quality is a very important factor for the survival of the company. Therefore, this research was conducted to apply quality control methods at the Company of Keripik Tempe Abadi in Malang City to improve the quality of their production. The tools used in this study are Seven tools and the table Failure Mode and Effect Analysis (FMEA). The results of this study indicate that there are product defects that exceed the tolerance limits of the company, namely in the form of deformities, broken products, burnt products, and defects in the packaging. Then based on the analysis with a Fishbone diagram to find out the root cause of product damage.